An analytical study of serum ferritin, vitamin D, and thyroid function in females with diffuse hair loss - Seema Rani; Anubhuti Chitkara; Prafulla K Sharma; Saket Sinha; Preeti Sharma (Wolters Kluwer Medknow Publications, 2022)
Objective: Women with diffuse hair loss need to be screened for possible causes or factors responsible for increased hair shedding and also to exclude factors that can increase hair shedding and aggravate the disease. Material and Methods: A prospective cross-sectional study of 40 cases (18-45years) of diffuse hair loss and 40 healthy females were included. The diagnosis was based on the detailed history, clinical examination to rule out pattern hair loss, and hair pull test. Complete hemogram, serum ferritin, vitamin D, and thyroid function tests (T3, T4, thyroid-stimulating hormone [TSH]) along with all routine investigations were determined for each participant. A diet history of vegetarians and non-vegetarians was also taken. Results: On screening, serum ferritin in cases ranged from 3.92 to 104 ng/mL with a mean of 22.36±23.10 ng/mL and that in controls ranged from 5.5 to115 ng/mL with a mean of 29.97±45.72 ng/mL. The serum ferritin level in cases was lower, at a cut-off value of 10 ng/mL, which is statistically significant (p= 0.027). For those with serum ferritin level >10 ng/mL, the mean concentration of hemoglobin was 11.65 ± 0.79 gm%, whereas for the <10 ng/mL serum ferritin level, the mean concentration of hemoglobin was 11 ± 1.1 gm% with a significant statistical difference (p= 0.027). The serum level of vitamin D in cases ranged from 8 to 57.4 IU/dL with a mean of 20.24±11.98 IU/dL while that in controls ranged from 11.1 to 42.6 IU/dL with a mean of 22.42±9.29 IU/dL, which was statistically significant difference (p= 0.003). We found no association of thyroid dysfunction with diffuse hair loss. On dietary evaluation, significant statistical association among vegetarians (67.5% cases and 40% controls) and non-vegetarians (32.5% cases and 60% controls) was observed (p= 0.024); however, we could not find any statistical significant association of diet with ferritin and vitamin D. Conclusion: Low ferritin and vitamin D may contribute to diffuse hair loss.